2021
DOI: 10.7225/toms.v10.n01.008
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Modelling of Marine Diesel Engine Cooling System

Abstract: Every internal combustion engine operates on the principle of converting thermal energy into mechanical work. During fuel combustion in the engine cylinders, the heat is released. It also has its negative effects; one is overheating of the engine cylinders and the engine in general. Since the engine parts are made of metal with its own thermal characteristics, the optimal temperature must be achieved in order to protect the components from overheating and, thus, from undesirable consequences of overheating. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The purpose of the engine room simulator (ERS), including actual ship features, is to make realistic analyses of the main engine and other systems in maritime training processes. ERS is also often preferred for examining and testing targeted situations used in academic studies (Rubio et al, 2018;Stavinuk et al, 2021). ERS was used for a fuel-water emulsion operating system to reduce exhaust gas emissions for a ship engine (Laskowski et al, 2015).…”
Section: Engine Room Simulatormentioning
confidence: 99%
“…The purpose of the engine room simulator (ERS), including actual ship features, is to make realistic analyses of the main engine and other systems in maritime training processes. ERS is also often preferred for examining and testing targeted situations used in academic studies (Rubio et al, 2018;Stavinuk et al, 2021). ERS was used for a fuel-water emulsion operating system to reduce exhaust gas emissions for a ship engine (Laskowski et al, 2015).…”
Section: Engine Room Simulatormentioning
confidence: 99%
“…A heat flow meter is used for heat flow measurements on small curved surfaces. Stanivuk et al [13] proposed a method to predict the maximum temperature and time constant inside different power cabins. Hoang et al [14] quantitatively confirmed whether the cooling system could meet the requirements of the power drive unit for the cooling temperature to be lower than 65°C through unit tests and one-dimensional simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various schemes of such systems with natural air or water cooling are used for marine power plants [1,2], for cars [3][4][5][6][7][8] and locomotives [9]. In addition, there are works [10,11], which consider engine cooling systems using refrigeration machines.…”
Section: Introductionmentioning
confidence: 99%